Uang Titik as a Land Utilization Contract in Mining: An Analysis of Justice and Legal Certainty from the Perspective of Islamic Economic Law - akhyar, akhyar (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2025)
The practice of ‘uang titik’ in artisanal gold mining activities in Hutabargot Sub-district is a form of unwritten contract between landowners and miners in land utilisation. The money point is given as an initial permit accompanied by a profit-sharing scheme of 20% for the landowner, while all risks are borne by the miner. This research aims to analyse the justice and legal certainty aspects of the practice of uang titik based on the perspective of sharia economic law. This research uses a qualitative approach with a normative-empirical method, through in-depth interviews, field observations, and literature studies. The results show that in principle, the practice of uang titik is acceptable in Islamic law through the 'urf approach, but there are inequalities in the distribution of risks and profits, as well as the absence of a written contract which creates legal uncertainty and potential injustice. Therefore, it is necessary to reformulate the contract with a fairer and more transparent approach to be in line with the principles of maqashid sharia, namely justice, protection of the rights of related parties, and environmental sustainability. This study recommends strengthening agreement documents and sharia law education for the community as applicable and sustainable solutions